Abnormal Bone Acquisition With Early‐Life HIV Infection: Role of Immune Activation and Senescent Osteogenic Precursors. (6th July 2016) - Manavalan, John S; Arpadi, Stephen; Tharmarajah, Shenthuraan; Shah, Jayesh; Zhang, Chiyuan A; Foca, Marc; Neu, Natalie; Bell, David L; Nishiyama, Kyle K; Kousteni, Stavroula; Yin, Michael T
ABSTRACT: Chronic immune activation associated with human immunodeficiency virus (HIV) infection may have negative consequences on bone acquisition in individuals infected with HIV early in life. Bone mineral density (BMD) and microarchitecture were characterized in 38 HIV‐infected men on antiretroviral therapy (18 perinatally‐infected, 20 adolescence‐infected) and 20 uninfected men age 20 to 25 years by dual‐energy X‐ray absorptiometry (DXA), high‐resolution peripheral quantitative computed tomography (HRpQCT). Flow cytometry was utilized to measure CD4+/CD8+ activation (HLADR+CD38+) and senescence (CD28–CD57+) and to quantify circulating osteogenic precursor (COP) cells in peripheral blood mononuclear cells using antibodies to RUNX2 and osteocalcin (OCN). Telomere lengths were measured in sorted COP cells using qPCR. DXA‐derived areal BMD Z ‐scores and HRpQCT‐derived volumetric BMD (vBMD) measures were lower in HIV‐infected than uninfected men. Proportion of activated and senescent CD4+ and CD8+ T cells were higher in HIV‐infected than uninfected men. The percentage of COP cells (mean ± SE) was lower in HIV‐infected than uninfected (0.19% ± 0.02% versus 0.43% ± 0.06%; p < 0.0001) men, and also lower in perinatally‐infected than adolescence‐infected men (0.15% ± 0.02% versus 0.22% ± 0.03%; p < 0.04). A higher proportion of COP cells correlated with higher bone stiffness, a measure of bone strength, whereas a higher proportion of activated CD4+ T cells correlated with lower BMD and stiffness and lower proportion of COP cells. T cell activation with HIV‐infection was associated with decreased numbers of osteogenic precursors as well as lower peak bone mass and bone strength. © 2016 American Society for Bone and Mineral Research.